A STUDY ON ENGLISH STUDENTS’ WILLINGNESS TO COMMUNICATE IN ENGLISH IN SOCIAL MEDIA - Yupika Maryansyah (Premise: Journal of English Education and Applied Linguistics, 2019)
This research aims to investigate factors affecting willingness to communicate in English in social media. This research was conducted in a descriptive method framework. Specifically, the research described factors that affect students' willingness to communicate in English in social media at English study program at the fourth semester of Muhammadiyah University of Bengkulu academic year 2018. The subjects of this research were fourth-semester students of English Education study program of Muhammadiyah University of Bengkulu Academic Year 2018 consisted of class A, B, and C.  The populations of the study were 77 students. The instruments used were questionnaire and interview. The data obtained from both questionnaire and interview were then analyzed by the process of checking, classifying, determining, and analyzing the data by using the percentage formula. The results of the study showed that there were five factors affecting willingness to communicate in English in social media. They were self-confidence, personality, motivation, attitude, and anxiety. The dominant factor was motivation since it had the highest percentage. In addition, the study also revealed some reasons why students have the willingness to communicate through social media.